ANALISIS TINGKAT LIKUIDITAS PADA PT. BANK KBBUKOPIN Tbk PERIODE 2018 - 2022 - Pielza Marshya Jelita Johanes, (2023)
Writing this Final Project Report aims to determine the level of liquidity at PT Bank KB Bukopin, Tbk for the 2018 - 2022 period using 3 (three) proxies, namely the Current Ratio, Quick Ratio, and Loan Deposit Ratio (LDR). The method used to analyze this ratio is using a descriptive quantitative approach and the data source used is secondary data taken from books, journals, OJK, and PBI. The financial data used is through annual financial reports which are accessed through the Bank KB Bukopin website for the period 2018 - 2022. The results of this liquidity ratio analysis show specific increases and decreases. The average Current Ratio is still in the criteria of being quite healthy, the Quick Ratio is in the criteria of being unhealthy and the Loan Deposit Ratio is in the criteria of being quite adequate.